Design performance and designer preference in an interactive, data-driven conceptual building design scenario. (May 2020) - Brown, Nathan C.
Abstract : Various interactive optimization techniques have been proposed to simultaneously consider quantitative and qualitative goals in conceptual architectural design. However, more research is required to understand the effects of these techniques on design processes and outcomes at the building scale, when substantial building performance simulations are considered. This paper presents a design study involving 34 participants who engaged with live feedback from surrogate models of structural and energy performance, while producing conceptual building geometries in several digital design environments. This study reveals that performance-enabled environments tend to improve simulated design objectives, while designers often prefer more flexibility than traditional automated optimization approaches when given the choice. Together, these preliminary findings encourage further development of interactive approaches to multi-objective early building design. Highlights: Surrogate model based live feedback often improved simulated design performance. Participants tended to prefer design environments with feedback but flexibility. Interactive feedback and optimization did not noticeably reduce design diversity. Interactive optimization techniques are still new to many architects and engineers. Interface improvements for future design tools can help increase their accessibility.